2009
DOI: 10.1055/s-0029-1217029
|View full text |Cite
|
Sign up to set email alerts
|

Cerium(III)-Mediated Efficient and Stereoselective Hydrochalcogenation of Terminal Alkynes

Abstract: C e r i u m (I I I)-M e d i a t e d H y d r o c h a l c o g e n a t i o n o f A l k y n e s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Some other recent protocols of interest, because they are related to the theme of this review, include the CeCl 3 -catalyzed hydrochalcogenation of propargylic alcohols and amines, the Cs-catalyzed addition of dichalcogenides to alkynes, and GaCl 3 -mediated disulfidation …”
Section: Catalytic Addition Of Rz−h Derivatives To Alkynes and Allene...mentioning
confidence: 99%
“…Some other recent protocols of interest, because they are related to the theme of this review, include the CeCl 3 -catalyzed hydrochalcogenation of propargylic alcohols and amines, the Cs-catalyzed addition of dichalcogenides to alkynes, and GaCl 3 -mediated disulfidation …”
Section: Catalytic Addition Of Rz−h Derivatives To Alkynes and Allene...mentioning
confidence: 99%
“…26 Recently, Silveira and coworkers have reported the first methodology of hydrochalcogenation of terminal alkynes promoted by CeCl 3 . 27 In the light of this background that we have studied a convenient procedure for transforming alkynes 9 into the corresponding alkenyl iodides10 using the CeCl 3 •7H 2 O-NaI system.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, to date, there are several efficient homogeneous and heterogeneous catalytic systems developed based on Pd, Ni, Rh, Au, Zr, Cu, and Cs to obtain various types of vinyl chalcogenides (branched and linear E or Z ) with excellent regio‐ and stereoselectivity starting from various terminal alkynes and thiols (both aromatic and aliphatic) . Large substrate scope and functional group tolerance, as well as the possibility to scale up the reactions and recycle the catalyst, make them highly useful and efficient tools for synthetic applications.…”
Section: Formation Of Monofunctionalized Akenes (Vinyl Chalcogenides)mentioning
confidence: 99%
“…Later Silveira et al found CeCl 3 to be an efficient catalyst for selectivea ddition of in-situ-formed selenolates and tellurolates to propargylic alcohols and amines resulting in linear products of Z-configuration (Scheme 21). [41] The solventh ad ac rucial effect on regioselectivity of the reaction, with the best results being achieved in iPrOH.T od ate, this is the only example of vinyl telluride formation via addition to the triple bond of alkynes.…”
Section: Catalytic Systems Leading To Anti-markovnikov-type (Linear) mentioning
confidence: 99%